2005
DOI: 10.1038/sj.bjp.0706416
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of metal ions in neurodegeneration: the basis for a promising therapeutic strategy

Abstract: The variety of factors and events involved in neurodegeneration renders the subject a major challenge. Neurodegenerative disorders include a number of different pathological conditions, which share similar critical metabolic processes, such as protein aggregation and oxidative stress, both of which are associated with the involvement of metal ions. In this review, Alzheimer's disease, Parkinson's disease and prion disease are discussed, with the aim of identifying common trends underlying these devastating neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
252
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(265 citation statements)
references
References 169 publications
2
252
0
5
Order By: Relevance
“…The exact physiological roles of PrP C are still under investigation, but many studies have suggested its participation in the metabolism of metals and its role as antioxidant (superoxide dismutase (SOD)-like activity). [6][7][8][9][10] Although the potential redox activity of PrP C has been previously demonstrated, this is controversial since other studies dispute the SOD function of PrP C . 11,12 The interaction of PrP C with metals such as iron (Fe), copper (Cu) and manganese (Mn) is important, since these metals serve as cofactors for enzymes, and play important roles in mammalian biochemical processes.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The exact physiological roles of PrP C are still under investigation, but many studies have suggested its participation in the metabolism of metals and its role as antioxidant (superoxide dismutase (SOD)-like activity). [6][7][8][9][10] Although the potential redox activity of PrP C has been previously demonstrated, this is controversial since other studies dispute the SOD function of PrP C . 11,12 The interaction of PrP C with metals such as iron (Fe), copper (Cu) and manganese (Mn) is important, since these metals serve as cofactors for enzymes, and play important roles in mammalian biochemical processes.…”
Section: Introductionmentioning
confidence: 93%
“…10,[17][18][19] Moreover, TSE neurotoxicity, associated with imbalance in brain homeostasis and deregulation of metals, has been previously observed for other neurodegenerative disorders such as Parkinson's disease (PD) and Alzheimer's disease (AD). 9 PrP C -metal interactions differ with each metal and may play a physiological or pathological role. For example, binding of PrP C to Cu is linked to PrP C stability and antioxidant activity at brain synapses, protecting the cells from oxidative damage and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and nitric oxide (NO . ) in addition to hydrogen peroxide (H 2 O 2 ) and peroxynitrite (ONOO -) [7]. These are highly unstable species that react with lipids, proteins, RNA and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Because all prion disorders except vCJD have a relatively long incubation period, effective treatment can be initiated much before clinical symptoms appear. Given the focus of this review, two possible avenues hold promise: (a) antioxidants and free radical scavengers (63,139,214), and (b) metal chelators (38,65,248). Limited studies conducted in this direction have been quite promising and are reviewed here.…”
mentioning
confidence: 99%